Case Report: Low-intensity transcranial focused ultrasound stimulation improves social interaction and stereotyped behavior in a boy with autism spectrum disorder - Cheng, Shu; Xu, Xuan; Yan, Chao Shan; Mao, Meng Chai; Luo, Kai Xuan; Zhang, Xiao Fan; Liang, Qi Hui; Long, Xiao Jing; Ao, Li Juan; Chen, Mo Xian (Frontiers in Psychiatry, 2025)
ObjectivesPresently, no biomedical therapies are available that specifically address the core symptoms of autism spectrum disorders. Given the evidence of cortical malfunction in ASD, low-intensity transcranial focused ultrasound stimulation has been discussed as a prospective therapeutic technique.MethodsWe describe the application of transcranial focused ultrasound to the left dorsolateral prefrontal cortex in a boy with ASD, which was applied for 30 minutes each consecutive weekday for four weeks (20 sessions in total). Social interaction, stereotyped behavior and language were assessed by scales before the first transcranial focused ultrasound session, immediately after 2 and 4 weeks of treatment. Besides, functional near-infrared spectroscopy was used to detect functional connections between regions of interest and the whole brain in individuals with ASD.ResultsScale assessments revealed several improvements in social and stereotypical behavior after low-intensity transcranial focused ultrasound. The results of functional near-infrared spectroscopy indicated increasing functional connections between the SM1 and other cortical regions as well as the whole brain, which accounted for the outcomes evaluated by the scale.ConclusionsLow-intensity transcranial focused ultrasound in ASD potentially rectified cortical dysfunction, thereby presenting a novel pathway for the advancement of biomedical interventions targeting the impaired social and stereotypical behaviors in ASD.